Enhancing Self-Confidence in Low-Income Adolescents Through Person-Centered Therapy: A Qualitative Case Study - Novia Purba; Lidia Kastanya; Sherly Sherly; Monika Monika; Valencia Christabel (IJIP : Indonesian Journal of Islamic Psychology, 2025)
Self-confidence is essential in adolescent development, particularly for social interactions, public speaking, and decision-making. Adolescents with low self-confidence often withdraw, feel anxious in social situations, and struggle with decisions. Previous research has linked self-confidence to both academic and social success. However, studies on effective psychological interventions to improve self-confidence in adolescents from low socioeconomic backgrounds remain scarce. This study focuses on a 19-year-old adolescent from an economically disadvantaged family. Despite academic potential and personal strengths, the subject experiences self-doubt and fear of self-expression. Person-centered therapy (PCT) was chosen as an appropriate intervention to enhance self-confidence. This research evaluates the effectiveness of PCT in promoting self-acceptance, positive self-perception, and confidence in social settings. Qualitative methods were employed to evaluate the effectiveness of the intervention. The findings indicate that PCT effectively boosts self-confidence, particularly through techniques such as unconditional positive regard. This supports the effectiveness of PCT in enhancing adolescent self-confidence and psychological well-being.